(untitled) (Research, Society and Development, 2021)
Objective: to analyze the influence that depressive symptoms have on obesity or excess weight, delimiting whether aspects such as gender and social factors are directly related to the condition. Methodology: research was carried out in the Virtual Health Library which includes the following databases: Nursing Database (BDENF), Analysis and Recovery System of Medical Literature (MEDLINE) and Latin American and Caribbean Literature in Sciences of Health (LILACS). Result: the final sample consisted of 13 articles, the oldest being published in 2015 and the most recent in 2020. Conclusion: the present study helps to understand the main factors identified in the literature as precursors of the relationship between depressive symptoms and obesity.